1985
DOI: 10.1029/ja090ia10p09763
|View full text |Cite
|
Sign up to set email alerts
|

Observations of limb radiance with Cryogenic Spectral Infrared Rocket Experiment

Abstract: A Spectral Infrared Rocket Experiment was launched from Poker Flat, Alaska, on September 28, 1977, to measure infrared emission spectra from the earth limb atmosphere. Spectrometers measured emission spectra from 1.40 to 16.5 µm during 12 vertical scans of the limb region (tangent heights 0 to 250 km) traversing the night, terminator, and day sectors of the limb atmosphere. The spectrometers were cryogenically cooled and telescoped for out‐of‐field rejection of the more intense radiation from lower altitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…The column density of OH is estimated to be 10 10 -10 11 cm −2 in the Ganymede atmosphere (Marconi 2007), which is comparable to that of the OH layer in the Earths atmosphere. However, the Ganymede SED, especially the non-detection at 3.6 μm, is difficult to explain by OH airglow because there is an emission band (Δν = 1) at 2.5-3.5 μm (Stair et al 1985) as shown in Figure 3, although the excitation state of OH molecules and chemical environment in the atmosphere Each data point of Ganymede in eclipse was obtained in the different date and impact parameter, thus the geometric relation among Jupiter, Ganymede, and the observer is different. Spectra of Jupiter (Rayner et al 2009) and the Earths atmosphere (Stair et al 1985) are also shown as a reference, scaled to the Ganymede brightness.…”
Section: Atmospheric Emission From the Satellitesmentioning
confidence: 99%
“…The column density of OH is estimated to be 10 10 -10 11 cm −2 in the Ganymede atmosphere (Marconi 2007), which is comparable to that of the OH layer in the Earths atmosphere. However, the Ganymede SED, especially the non-detection at 3.6 μm, is difficult to explain by OH airglow because there is an emission band (Δν = 1) at 2.5-3.5 μm (Stair et al 1985) as shown in Figure 3, although the excitation state of OH molecules and chemical environment in the atmosphere Each data point of Ganymede in eclipse was obtained in the different date and impact parameter, thus the geometric relation among Jupiter, Ganymede, and the observer is different. Spectra of Jupiter (Rayner et al 2009) and the Earths atmosphere (Stair et al 1985) are also shown as a reference, scaled to the Ganymede brightness.…”
Section: Atmospheric Emission From the Satellitesmentioning
confidence: 99%
“…tion (SISSI)) [e.g., Stair et al, 1975Stair et al, , 1983Stair et al, , 1985Smith et al, 1990;Vollmann and Grossmann, 1998], and also from space by the C!RRIS 1-A experiment on the Space Shuttle [Lee et al, 1991]. Among these data, those analyzed in most detail are the SPIRE measurements [Nebel et al, 1994].…”
mentioning
confidence: 99%
“…Since only 2.4 % of the N 2 molecules participate in the RV energy transfer process, the rate coefficient for deactivation of CO 2 (v 2 ) by N 2 would be k VT (N 2 ) = ((2.32 ± 1.1) × 0.024) × 10 −12 = (5.6 ± 2.6) × 10 −14 . A larger calculated rate coefficient k N 2 would not be a problem, since the v 2 mode of CO 2 at least up to 90 km altitude is in local thermodynamic equilibrium (LTE); i.e., its vibrational temperature is nearly the same as the translational temperature (Feofilov et al, 2012;Stair et al, 1985). Tables 1a-d, using the atmospheres, provided by Feofilov and López-Puertas, give the rate coefficients k VT (N 2 ), the fifth column, and k VR (N 2 ), the last column, required by k x given by these atmospheres.…”
Section: Thermal Rotational Levelsmentioning
confidence: 99%
“…In the chemical literature, the rate coefficients of the reactions are given in the exothermic direction (reverse of Reaction 1a), and we will follow that convention. The room temperature value of the rate coefficient k ATM for the exothermic process derived by modeling the 15 µm emission, observed by the Spectral Infrared Rocket Experiment (SPIRE) (Stair et al, 1985) from the MLT region of the atmosphere, is 5×10 −13 cm 3 s −1 (Sharma and Nadile, 1981), 5.2 × 10 −12 cm 3 s −1 (Stair et al, 1985), 3.5 × 10 −12 cm 3 s −1 (Sharma, 1987), and (3 − 9) × 10 −12 cm 3 s −1 (Sharma and Wintersteiner, 1990). These studies gave values of k ATM that are 1-2 orders of magnitude greater than values recommend earlier (Crutzen, 1970;Taylor, 1974).…”
Section: Introductionmentioning
confidence: 99%